Ritual Performance as Cultural Memory Work: Re-enacting History, Sacred Landscapes, and Spiritual Ecology in the Nyiar Lumar Ritual of Kawali - Ciamis: - Fikri Ahmad Maulana; Dadan Ramdani; Gina Tsania Salsabila (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2026)
This study examines Nyiar Lumar as a form of ritual performance that functions as cultural memory work in reconstructing history, sacralizing landscape, and shaping collective spirituality in the Kawali community of West Java, Indonesia. Drawing on cultural memory theory, performance studies, and spiritual ecology, the research employs a qualitative approach combining performance ethnography, participant observation, in-depth interviews, and symbolic analysis. The findings demonstrate that the historical narrative of the Palagan Bubat is transformed into a moral and identity-bearing symbol through embodied performance, rather than reproduced as a fixed historical account. The Astana Gede site operates as a sacred landscape mediating relationships between humans, nature, and ancestral memory, enabling ritual experience to generate ecological awareness and spiritual reflection. Egalitarian communal participation reinforces the transmission of ancestral values, social cohesion, and cultural resilience. This study advances scholarship by conceptualizing ritual performance as an integrative practice in which historical memory, artistic expression, and ecological ethics are mutually constituted. By foregrounding an Indonesian case rarely discussed in international literature, the article contributes empirical depth and theoretical insight to debates in cultural memory studies, performance studies, and heritage scholarship on the interconnections between ritual, environment, and spirituality